Pragmatics: Mapping Evidence on Enhancing Children's Use of Linguistic and Non-Linguistic Capacities for Interactive Communication - Ahmed Alduais; Issa Al-Qaderi; Najla Alfadda; Hind Alfadda (MDPI AG, 2022)
New-born infants communicate from the first minute they come to life. This non-linguistic and non-verbal capacity to interact from the first day they come to life enables them to express their needs and evidence their typical development. This capacity to interact develops to include linguistic and non-linguistic use of verbal and non-verbal interaction, that is, pragmatics. Because pragmatics is heterogeneously structured of semiotic, cognitive, motor and sensory elements so it is vital to ensure successful human interaction. The other language elements (i.e., phonological, morphological, syntactic and semantic) are essential inputs for this human interaction outcome (i.e., pragmatics). Accordingly, this study sought to map evidence that pragmatics can enhance children's use of linguistic and non-linguistic capacities for interactive communication. This was addressed by conducting bibliometric and scientometric analyses of 6554 documents from Scopus, 1167 from WOS and 11,230 from Lens between 1939 and 2022. We analysed the past, present and future developments of the field of pragmatics using bibliometric and scientometric indicators. The scientometric analysis was conducted using CiteSpace 5.8.R3 and VOSviewer 1.6.18 software, which enabled the tabulation, visualisation and measurement of the impact of central influencers in the field of pragmatics. In the light of our results, pragmatics continues to expand in order to understand human interaction in a deeper way and to enhance children's typical interactions with the environment around them. The group should also include adults or elderly people whose pragmatic language skills have been impaired due to any acquired or developmental disorder, such as a brain injury.